2019
DOI: 10.1101/850453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning mutational signatures and their multidimensional genomic properties with TensorSignatures

Abstract: Key findings• Simultaneous inference of mutational signatures across mutation types and genomic features refines signature spectra and defines their genomic determinants • Two distinct mutational signatures of UV exposure found in active and quiescent chromatin, which may be attributed to differential activity of nucleotide excision repair • Transcription-associated mutagenesis manifesting as A[T>C] mutations is found in a range of cancer types • APOBEC mutagenesis produces two signatures reflecting highly clu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
(52 reference statements)
1
23
0
Order By: Relevance
“…Using the trinucleotide context of each mutation, four single-base substitution reference to genomic context (11). It has been hypothesised that SBS7c and SBS7d may be due to translesion DNA synthesis by error-prone polymerases inserting T rather than A, or G rather than A, opposite UV damage respectively (10).…”
Section: Mutant Gene Selection and Mutational Signature Vary Across Tmentioning
confidence: 99%
“…Using the trinucleotide context of each mutation, four single-base substitution reference to genomic context (11). It has been hypothesised that SBS7c and SBS7d may be due to translesion DNA synthesis by error-prone polymerases inserting T rather than A, or G rather than A, opposite UV damage respectively (10).…”
Section: Mutant Gene Selection and Mutational Signature Vary Across Tmentioning
confidence: 99%
“…Thus, we might expect MMR deficiency to be associated with distinct mutational signatures, with mutation rates varying by specific base changes, indels, local sequence context and replication strand. To assess this, we extracted mutational signatures jointly for all microdissected samples, including both healthy and neoplastic, using the TensorSignatures algorithm (Vöhringer et al, 2020).…”
Section: Mmr Repairs Replication-dependent and Independent Dna Damagementioning
confidence: 99%
“…TensorSignatures (Vöhringer et al, 2020) (Pich et al, 2018). Clustered SBS were identified using a 2-state Hidden-Markov model (Vöhringer et al, 2020).…”
Section: Mutational Signature Extractionmentioning
confidence: 99%
“…For the transcription strand asymmetry, coding and template strand were obtained from a published study 53 and the asymmetry is reported as log2 ratio of (mutation count within template regions) / (mutation counts within coding regions).…”
Section: Methodsmentioning
confidence: 99%